Financial reporting behaviour and firm’s economic success: Malaysian evidence - Nor Irdawati Mahyuddin,; Hairul Suhaimi Nahar,; Yusniyati Yusri, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The emergence of modern corporate landscape, with regard to the way firms are managed and controlled, creates a variety of financial reporting issues. Empirical results in prior studies have been inconclusive, as to whether financial reporting behaviours i.e. earnings management activities are detrimental to firms’ economic success (proxied by its future performance). Some have argued that managing earnings are intended to achieve better future performance rather than being opportunistic in nature. This study aims to empirically investigate whether managing earnings to meet earnings target has any affect on firms’ future performance in Malaysia. In extending prior work in the earnings management area, by incorporating discretionary reporting behaviour element to provide better view of Malaysian firms’ financial reporting behaviours across 2001–2015 reporting horizon, we find that real-based earnings management led to lower firm’s future performance. This supports the agency theory prediction that firms which engage in real reporting opportunistically would negatively affect their future economic performance. This, however, does not hold true for accruals earnings management. The empirical results suggest that different mechanisms of financial reporting behaviour, of either discretionary or real in nature, provide different implications on the firms’ future performance. The paper adds to the growing body of empirical knowledge in financial reporting behaviours and firms’ economic success in an emerging economy like Malaysia.